Modeling H2-enriched dual fuel engine performance and emissions - Jayagopal Narayanan; Y. V. V. Satyanarayana Murthy; Sandeep Kumar; Talari Surendra; Ram Mohan Rao Madaka (Institute of Advanced Engineering and Science, 2026)
This study utilizes a validated GT-Power simulation model to evaluate hydrogen (H2) enrichment effects on the performance and emissions of a four-cylinder, 86 kW dual-fuel diesel engine. The primary goal is identifying operating strategies that enhance efficiency while maintaining nitrogen oxide (NOx) emissions at or below baseline levels, termed